The Impact of Macrokinetic Effects on the Heck‐Matsuda Reaction Using in‐situ Generated and Immobilized Pd‐Catalysts. Issue 39 (19th October 2022) - Matelienė (née Dauksaîtė), Lauryna; Gu, Xiaoting; Brunner, Heiko
Abstract: T he present study shows the influence of stirring speed on the kinetics of the Heck‐Matsuda reaction when using in‐situ generated immobilized catalysts and olefins. The stirring speed not only influences the reaction kinetics of the actual reaction, but also the particle size distribution and the degree of immobilization of the palladium clusters. In addition to the stirring speed, the electronic nature of the olefin used in each case also plays a decisive role on the particle size distribution and thus the catalytic activity of the system. Abstract : It's the agitation that matters: the stirring speed influences the kinetics of the Heck‐Matsuda reaction when using in‐situ generated immobilized catalysts and olefins. The stirring speed not only influences the reaction kinetics of the actual reaction, but also the particle size distribution and the degree of immobilization of the palladium clusters. In addition to the stirring speed, the electronic nature of the olefin used in each case also plays a decisive role on the particle size distribution and thus the catalytic activity of the system.